Material with antiferromagnetic metallic property and preparation and application thereof
By preparing the lanthanide-doped calcium-cobalt oxide material RxA1-xBO3, the problem of scarcity of antiferromagnetic metallic materials in the prior art is solved, and the controllable modulation of the antiferromagnetic sequence of the material is achieved under a high magnetic field, with metal behavior and in-plane controllable characteristics.
Patent Information
- Application Number
- CN202311167672.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-09-11
AI Technical Summary
There are very few materials with antiferromagnetic metal properties in existing materials, especially among oxides. There are only a handful of materials that can effectively regulate the magnetic sequence by external magnetic fields.
A material having antiferromagnetic metallic properties is provided, and the general formula is RxA1-xBO3, wherein R is a lanthanide element and the value of x is within 0.01 to 0.30; A is selected from the main group IIA element, and B is selected from the 3d transition metal element. By annealing the ferromagnetic semiconductor material RxA1-xBO2.5 in an atmosphere containing oxygen radicals, RxA1-xBO3 material with antiferromagnetic performance was prepared.
It realizes the conversion of the antiferromagnetic sequence of the material into a ferromagnetic sequence under a high magnetic field, and restores the antiferromagnetic sequence after the external magnetic field is removed. It has an in-plane controllable antiferromagnetic metal state, providing new material preparation methods and application prospects.
Smart Images

Figure CN119612606A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to, but is not limited to, a material having antiferromagnetic metallic properties, and in particular to, but is not limited to, a material having antiferromagnetic metallic properties and its preparation and application. Background Art
[0002] Magnetic materials in nature can be divided into ferromagnets (ferrimagnets) and antiferromagnets according to whether they contribute to macroscopic magnetic moments. Due to different conductive mechanisms, ferromagnetic materials generally behave like metals, while antiferromagnetic materials generally behave like insulating materials. From the perspective of basic scientific research and application, it is of great significance to find "abnormal" ferromagnetic materials with insulating behavior and antiferromagnetic materials with metallic behavior. Currently, materials confirmed as antiferromagnetic metals are extremely rare, but they all show rich physical properties and application prospects. For example, MnBi 2 Te 4 The magnetic ground state of this material exhibits antiferromagnetism along the c-axis direction. The antiferromagnetic order can be converted into ferromagnetic order through the magnetic field in the c-axis direction. This material is also the first discovered intrinsic antiferromagnetic topological insulator material, which can realize the quantum anomalous Hall effect at higher temperatures.
[0003] Existing materials with antiferromagnetic metallic properties are extremely rare, and a large part of them are two-dimensional van der Waals materials, which are even rarer in oxides. Among these materials, there are only a handful of materials in which the antiferromagnetic order can achieve effective regulation of the magnetic order by an external magnetic field. Summary of the invention
[0004] The following is a summary of the subject matter described in detail herein. This summary is not intended to limit the scope of the claims.
[0005] In an embodiment of the present disclosure, a material having antiferromagnetic metallic properties is provided. The general formula of the material is R x A 1-x BO 3 , wherein R is a lanthanide element; the value of x is within a range of 0.01 to 0.30;
[0006] The A is selected from the group IIA elements, such as Ca and Sr, and the B is selected from the group 3d transition metal elements, such as Fe, Co and Ni;
[0007] Observing along the c-axis direction of the crystal structure, the atomic structure of the material is a stacking of octahedral layers (limonite structure).
[0008] In some embodiments provided by the present disclosure, the material is selected from Gd 0.1 Ca 0.9 CoO 3 ,La 0.1 Ca 0.9 CoO3 、Nd 0.1 Ca 0.9 CoO 3 、Sm 0.1 Ca 0.9 CoO 3 、Dy 0.1 Ca 0.9 CoO 3 , Er 0.1 Ca 0.9 CoO 3 He Lu 0.1 Ca 0.9 CoO 3 Any one or more of La-based element doping. In some embodiments provided by the present disclosure, the antiferromagnetism of the material is manifested as having an antiferromagnetic effect along the ab plane direction of the crystal structure.
[0009] In some embodiments provided in the present disclosure, the method for preparing the material having antiferromagnetic metallic properties comprises:
[0010] The ferrimagnetic semiconductor material R x A 1-x BO 2.5 Annealing in an atmosphere containing oxygen free radicals;
[0011] The ferrimagnetic semiconductor material R x A 1-x BO 2.5 R is a lanthanide element, and the value of x is within a range of 0.01 to 0.30; A is selected from the elements of the IIA main group, and B is selected from 3d transition metal elements.
[0012] In some embodiments provided by the present disclosure, the annealing rate is 1° C. / min to 3° C. / min.
[0013] In some embodiments provided in the present disclosure, the ferrimagnetic semiconductor material R x A 1-x BO 2.5 Annealing at 250°C to 300°C;
[0014] In some embodiments provided in the present disclosure, the ferrimagnetic semiconductor material R x A 1-x BO 2.5 The annealing time is 3h to 7h.
[0015] In some embodiments provided in the present disclosure, the ferrimagnetic semiconductor material R x A 1-x BO 2.5The atomic structure of the material is an alternating stacking structure of one layer of BO tetrahedron and one layer of BO octahedron along the c-axis direction of the crystal structure (limonite structure).
[0016] In some embodiments provided in the present disclosure, the ferrimagnetic semiconductor material R x A 1-x BO 2.5 The growth is in the form of a thin film on the substrate surface. Annealing itself has no restrictions on the shape and size of the material.
[0017] In some embodiments provided in the present disclosure, the ferrimagnetic semiconductor material R x A 1-x BO 2.5 The thickness of the film is 2nm to 500nm.
[0018] In some embodiments provided in the present disclosure, the ferrimagnetic semiconductor material R x A 1-x BO 2.5 The preparation method comprises:
[0019] Using R x A 1-x BO 2.5 The target material is formed on the surface of the substrate by any of physical vapor deposition, chemical vapor deposition, electroplating, vacuum thermal evaporation, vacuum electron beam evaporation, DC sputtering, magnetron sputtering, radio frequency sputtering or pulsed laser deposition. x A 1-x BO 2.5 .
[0020] In some embodiments provided in the present disclosure, the R x A 1-x BO 2.5 The preparation method of the target material comprises: mixing the oxide of R, the oxide of A and the oxide of B according to R x A 1-x BO 2.5 The R x A 1-x BO 2.5 Target material.
[0021] In some embodiments provided by the present disclosure, the substrate is made of a material having any one of (001) orientation, (110) orientation and (111) orientation.
[0022] In some embodiments provided in the present disclosure, the substrate YAlO 3 、SrTiO 3 、LaAlO 3 、(LaAlO 3) 0.3 -(SrAl 0.5 Ta 0.5 O 3 ) 0.7 and LaSrAlO 4 Any one or more of the common substrates.
[0023] In another aspect, the present disclosure provides a method for controlling the magnetic order of the material having antiferromagnetic metallic properties, the method comprising:
[0024] Applying an external magnetic field to the material along the ab plane direction of the atomic structure of the material to transform the antiferromagnetic order of the material into a ferromagnetic order;
[0025] After the external magnetic field is removed, the ferromagnetic order of the material transforms back to an antiferromagnetic order.
[0026] The material with antiferromagnetic metallic property provided by the present disclosure is a rare material in oxides with controllable in-plane (vertical to the surface of thin film sample) antiferromagnetic metallic state.
[0027] On the other hand, the embodiments of the present disclosure provide the application of the above-mentioned material with antiferromagnetic metallic properties in any one or more of logic devices, memory devices, catalytic materials, electromagnetic wave transmitters, electromagnetic wave receivers and photoelectric conversion elements.
[0028] The beneficial effects of the present disclosure over the prior art include:
[0029] The present disclosure provides a new material with a controllable antiferromagnetic metallic state in a plane, and provides a new method to prepare such a material. The material has a high conductivity and a controllable antiferromagnetic order in the ab plane, and can be transformed into a ferromagnetic order under a high magnetic field. The antiferromagnetic order in the material is modulated in a controllable magnetic field.
[0030] Other features and advantages of the present disclosure will be described in the following description, and partly become apparent from the description, or be understood by implementing the present disclosure. Other advantages of the present disclosure can be invented and obtained by the schemes described in the description. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings are used to provide an understanding of the technical solution of the present disclosure and constitute a part of the specification. Together with the embodiments of the present disclosure, they are used to explain the technical solution of the present disclosure and do not constitute a limitation on the technical solution of the present disclosure.
[0032] Figure 1 For R 0.1 Ca 0.9 CoO 2.5 (Left) and R 0.1 Ca0.9 CoO 3 (Right) Schematic diagram of the atomic structure.
[0033] Figure 2 LaAlO 3 Gd on (001) substrate 0.1 Ca 0.9 CoO 2.5 and Gd 0.1 Ca 0.9 CoO 3 X-ray diffraction (XRD) patterns of thin films, 2θ / ω scans.
[0034] Figure 3 This is the curve of magnetization intensity (M) changing with magnetic field (H) and temperature (T). Figure 3 The corresponding test temperature in (a) is 30K, and the test in (b) is the test result of the heating process after the temperature drops from room temperature to 10K under 1kOe magnetic field.
[0035] Figure 4 Gd 0.1 Ca 0.9 CoO 3 The resistivity curve of the film changes with temperature.
[0036] Figure 5 For R 0.1 Ca 0.9 CoO 3 Curve of the in-plane magnetization intensity (M) of the film changing with the magnetic field (H), corresponding to the test temperature of 50K, where R = La, Nd, Sm, Gd, Dy, Er, Lu. DETAILED DESCRIPTION
[0037] To make the purpose, technical solution and advantages of the present disclosure more clear, the embodiments of the present disclosure are described in detail below. It should be noted that the embodiments and features in the embodiments of the present disclosure can be combined with each other arbitrarily without conflict.
[0038] The R used in the embodiments and comparative examples of the present disclosure 0.1 A 0.9 BO 2.5 The target material preparation method includes:
[0039] The oxides of R, A and B are separated according to R x A 1-x BO 2.5 The mixed powders are uniformly mixed according to the stoichiometric ratio, pressed into a certain shape and size, sintered at 1200°C in an atmospheric environment for 12 hours, and then annealed at a rate of 200°C / h to obtain the R x A 1-x BO2.5 Target material.
[0040] Embodiment 1:
[0041] In the LaAlO 3 Preparation of thin film ferrimagnetic semiconductor material Gd on (001) substrate by pulsed laser deposition system 0.1 Ca 0.9 CoO 2.5 , Gd 0.1 Ca 0.9 CoO 2.5 The thickness is 2nm to 500nm. The atomic structure of the material is as follows Figure 1 As shown in the left figure, the crystal structure is observed along the c-axis. The grown Gd 0.1 Ca 0.9 CoO 2.5 It has a structure with one layer of Co-O tetrahedron and one layer of Co-O octahedron stacked alternately, which exhibits ferrimagnetic semiconductor behavior.
[0042] Gd 0.1 Ca 0.9 CoO 2.5 Annealing at 300°C in an atmosphere containing oxygen free radicals at 1°C / min to 3°C / min for 3h to 7h yields Gd 0.1 Ca 0.9 CoO 3 , the atomic structure is as Figure 1 As shown in the middle right figure, when observed along the c-axis direction of the crystal structure, all octahedral layers are stacked, among which 10% of the Ca ions are replaced by Gd ions to show preferential site doping. The material has antiferromagnetic metallic behavior that can be controlled by an external magnetic field along the ab plane direction of the crystal structure.
[0043] Embodiment 2:
[0044] Using the process method of Example 1, the LaAlO 3 Thin film ferrimagnetic semiconductor material La prepared on (001) substrate 0.1 Ca 0.9 CoO 2.5 (Compared to Gd in Example 1 0.1 Ca 0.9 CoO 2.5 have the same crystal structure), La 0.1 Ca 0.9 CoO 2.5 Annealing at 300°C in an atmosphere containing oxygen free radicals yields La 0.1 Ca 0.9 CoO 3 (Compared with the Gd prepared in Example 1 0.1 Ca 0.9CoO 3 Having the same crystal structure) has antiferromagnetic metallic behavior that can be controlled by an external magnetic field along the ab plane direction of the crystal structure.
[0045] Embodiment 3:
[0046] Using the process method of Example 1, the LaAlO 3 Thin film ferrimagnetic semiconductor material Nd prepared on (001) substrate 0.1 Ca 0.9 CoO 2.5 (Compared to Gd in Example 1 0.1 Ca 0.9 CoO 2.5 have the same crystal structure), Nd 0.1 Ca 0.9 CoO 2.5 Annealing at 300°C in an atmosphere containing oxygen radicals yields Nd 0.1 Ca 0.9 CoO 3 (Compared with the Gd prepared in Example 1 0.1 Ca 0.9 CoO 3 Having the same crystal structure) has antiferromagnetic metallic behavior that can be controlled by an external magnetic field along the ab plane direction of the crystal structure.
[0047] Embodiment 4:
[0048] Using the process method of Example 1, the LaAlO 3 Thin film ferrimagnetic semiconductor material Sm prepared on (001) substrate 0.1 Ca 0.9 CoO 2.5 (Compared to Gd in Example 1 0.1 Ca 0.9 CoO 2.5 have the same crystal structure), Sm 0.1 Ca 0.9 CoO 2.5 Annealing at 300 °C in an atmosphere containing oxygen free radicals yields Sm 0.1 Ca 0.9 CoO 3 (Compared with the Gd prepared in Example 1 0.1 Ca 0.9 CoO 3 Having the same crystal structure) has antiferromagnetic metallic behavior that can be controlled by an external magnetic field along the ab plane direction of the crystal structure.
[0049] Embodiment 5:
[0050] Using the process method of Example 1, the LaAlO 3Thin film ferrimagnetic semiconductor material Dy prepared on (001) substrate 0.1 Ca 0.9 CoO 2.5 (Compared to Gd in Example 1 0.1 Ca 0.9 CoO 2.5 have the same crystal structure), Dy 0.1 Ca 0.9 CoO 2.5 Annealing at 300°C in an atmosphere containing oxygen free radicals yields Dy 0.1 Ca 0.9 CoO 3 (Compared with the Gd prepared in Example 1 0.1 Ca 0.9 CoO 3 Having the same crystal structure) has antiferromagnetic metallic behavior that can be controlled by an external magnetic field along the ab plane direction of the crystal structure.
[0051] Embodiment 6:
[0052] Using the process method of Example 1, the LaAlO 3 Thin film ferrimagnetic semiconductor material Er prepared on (001) substrate 0.1 Ca 0.9 CoO 2.5 (Compared to Gd in Example 1 0.1 Ca 0.9 CoO 2.5 have the same crystal structure), Er 0.1 Ca 0.9 CoO 2.5 Annealing at 300°C in an atmosphere containing oxygen free radicals yields Er 0.1 Ca 0.9 CoO 3 (Compared with the Gd prepared in Example 1 0.1 Ca 0.9 CoO 3 Having the same crystal structure) has antiferromagnetic metallic behavior that can be controlled by an external magnetic field along the ab plane direction of the crystal structure.
[0053] Embodiment 7:
[0054] Using the process method of Example 1, the LaAlO 3 Thin film ferrimagnetic semiconductor material Lu prepared on (001) substrate 0.1 Ca 0.9 CoO 2.5 (Compared to Gd in Example 1 0.1 Ca 0.9 CoO 2.5 have the same crystal structure), Lu0.1 Ca 0.9 CoO 2.5 Annealing at 300°C in an atmosphere containing oxygen radicals yielded Lu 0.1 Ca 0.9 CoO 3 (Compared with the Gd prepared in Example 1 0.1 Ca 0.9 CoO 3 Having the same crystal structure) has antiferromagnetic metallic behavior that can be controlled by an external magnetic field along the ab plane direction of the crystal structure.
[0055] In summary, through the characterization of the above-mentioned various La-based element-doped samples, it can be concluded that all specific ratios of La-based element-doped calcium cobalt oxide materials have antiferromagnetic metallic behaviors that can be controlled by an external magnetic field along the ab plane. The results of Examples 1 to 7 are summarized in Figure 5 .
[0056] Comparative Example 1:
[0057] The difference between this comparative example and Example 1 is that the atmosphere containing oxygen free radicals in Example 1 is replaced by pure oxygen. The other processes are exactly the same as those in Example 1.
[0058] R cannot be obtained in pure oxygen 0.1 Ca 0.9 CoO 3 (R=La series elements) materials will not have antiferromagnetic metal properties that can be controlled by external magnetic fields along the ab plane direction.
[0059] In addition, the ratio of R between ~0.01 and ~0.30 can realize antiferromagnetic metallic properties with controllable external magnetic field along the ab plane direction, corresponding to the ratio of Ca from ~0.99 to ~0.70.
[0060] Figure 2 , Figure 3 and Figure 4 The specific experimental data are all taken from the Gd prepared in Example 1 0.1 Ca 0.9 CoO 3 The film and other doped materials with La series elements in the same proportion have similar properties.
[0061] By using the 2θ / ω scan of an X-ray diffractometer (XRD), information about the out-of-plane lattice period of the entire sample can be obtained. Figure 2 As shown, in LaAlO 3 R grown on (001) substrate 0.1 Ca 0.9 CoO 2.5 (R = La-based element Gd) film, and R after ozone annealing at 300°C for three hours 0.1Ca 0.9 CoO 3 (R = La-based element Gd) film. According to the Bragg diffraction formula, the out-of-plane lattice constant changes from 1.513nm to 0.371nm, and the out-of-plane period changes from 4 Co-O layers to 1 Co-O octahedral layer. This indicates that the entire sample has been completely oxidized, and a uniform and high-quality R 0.1 Ca 0.9 CoO 3 (R = La-based element Gd) thin film.
[0062] The R 0.1 Ca 0.9 CoO 3 The macroscopic magnetic properties of the (R = La-based element Gd) film were measured, and the experimental results are as follows Figure 3 As shown in Figure 1, the material has obvious antiferromagnetic behavior at low temperature and low field. Figure 3 (a) is the hysteresis loop of the magnetization intensity (M) at 30K as the magnetic field (H) changes. The direction of the magnetic field is along the ab plane (i.e., in-plane) direction of the atomic structure of the material. Under low magnetic fields, the magnetization intensity increases slowly and linearly with the magnetic field. As the magnetic field increases, after exceeding the critical magnetic field, the magnetization intensity increases sharply and eventually changes to a ferromagnetic state. This result shows that through a certain magnetic field (about 45kOe at this temperature), the original antiferromagnetic ground state of the material can be artificially modulated into a ferromagnetic excited state. This controllable magnetic field will play a great role in the field of self-selected electronics. The antiferromagnetic transition temperature of the material is as follows: Figure 3 (b) shows that it is about 55K.
[0063] The physical properties comprehensive test system (PPMS) was used to test R 0.1 Ca 0.9 CoO 3 The resistivity of the thin film (R = La series element Gd) is measured, such as Figure 4 As shown, the R obtained by ozone treatment 0.1 Ca 0.9 CoO 3 (R=La-based element Gd) The resistivity decreases significantly as the temperature decreases, and the absolute value is very small. Its resistivity can reach below 500μΩ·cm, which clearly shows metallic properties.
[0064] Antiferromagnetic metal materials have occupied an important position in the application of spin electronics devices due to their superior performance. Compared with ferromagnetic materials, antiferromagnetic metal materials have strong anti-interference ability to external magnetic fields, do not generate stray fields, have faster response capabilities, and can produce greater magnetic transport effects. The advantages brought by these properties in terms of energy consumption and size have made antiferromagnetic metal materials receive unprecedented attention in the field of highly integrated magnetic devices such as disk read heads and magnetic random access memory (MRAM). In addition, in the next generation of electronic spin devices studied in the laboratory, antiferromagnetic metal materials are gradually replacing the position of ferromagnetic materials. A large number of spin logic devices based on antiferromagnetic properties have been proposed and tested. It is believed that more antiferromagnetic devices will be used in industry in the near future.
Claims
1. A material having antiferromagnetic metallic properties, characterized in that: The general formula of the material is R x A 1-x BO3, wherein R is a lanthanide element; and x is within a range of 0.01 to 0.30; A is selected from the elements of the main group IIA, and B is selected from 3d transition metal elements; Observing along the c-axis direction of the crystal structure, the atomic structure of the material is a stacking of octahedral layers.
2. The material having antiferromagnetic metallic properties according to claim 1, wherein the material is selected from Gd 0.1 Ca 0.9 CoO3、La 0.1 Ca 0.9 CoO3、Nd 0.1 Ca 0.9 CoO3、Sm 0.1 Ca 0.9 CoO3、Dy 0.1 Ca 0.9 CoO3、Er 0.1 Ca 0.9 CoO3 and Lu 0.1 Ca 0.9 Any one or more of CoO3.
3. The method for preparing the material having antiferromagnetic metallic properties according to claim 1, characterized in that: The preparation method comprises: The ferrimagnetic semiconductor material R x A 1-x BO 2.5 Annealing in an atmosphere containing oxygen free radicals; The ferrimagnetic semiconductor material R x A 1-x BO 2.5 R is a lanthanide element, and the value of x is within a range of 0.01 to 0.30; A is selected from the elements of the main group IIA, and B is selected from 3d transition metal elements; The ferrimagnetic semiconductor material R x A 1-x BO 2.5 The atomic structure of the quartz crystal is an alternating stacking structure of one layer of BO tetrahedron and one layer of BO octahedron along the c-axis direction of the crystal structure.
4. The preparation method according to claim 3, characterized in that: The annealing rate is 1°C / min to 3°C / min; Optionally, the ferrimagnetic semiconductor material R x A 1-x BO 2.5 Annealing at 250°C to 300°C; Optionally, the ferrimagnetic semiconductor material R x A 1-x BO 2.5 The annealing time is 3h to 7h.
5. The preparation method according to claim 3 or 4, characterized in that: The ferrimagnetic semiconductor material R x A 1-x BO 2.5 It grows on the substrate surface in the form of a thin film; Optionally, the ferrimagnetic semiconductor material R x A 1-x BO 2.5 The thickness of the film is 2nm to 500nm.
6. The preparation method according to claim 3 or 4, characterized in that: The ferrimagnetic semiconductor material R x A 1-x BO 2.5 The preparation method comprises: Using R x A 1-x BO 2.5 The target material is formed on the surface of the substrate by any of physical vapor deposition, chemical vapor deposition, electroplating, vacuum thermal evaporation, vacuum electron beam evaporation, DC sputtering, magnetron sputtering, radio frequency sputtering or pulsed laser deposition. x A 1-x BO 2.5 .
7. The preparation method according to claim 6, characterized in that: The R x A 1-x BO 2.5 The target material preparation method includes: The oxides of R, A and B are separated according to R x A 1-x BO 2.5 The R x A 1-x BO 2.5 Target material.
8. The preparation method according to claim 6, characterized in that: The material of the substrate is selected from materials with any one of (001) orientation, (110) orientation and (111) orientation; Optionally, the substrate is selected from YAlO3, SrTiO3, LaAlO3, (LaAlO3) 0.3 -(SrAl 0.5 Ta 0.5 O3) 0.7 and LaSrAlO4, any one or more thereof.
9. The method for controlling the magnetic order of a material having antiferromagnetic metallic properties according to claim 1 or 2, characterized in that: The magnetic order control method comprises: Applying an external magnetic field to the material along the ab plane direction of the atomic structure of the material to transform the antiferromagnetic order of the material into a ferromagnetic order; After the external magnetic field is removed, the ferromagnetic order of the material transforms back to an antiferromagnetic order.
10. Application of the material with antiferromagnetic metallic properties as claimed in claim 1 or 2 in any one or more of logic devices, memory devices, catalytic materials, electromagnetic wave transmitters, electromagnetic wave receivers and photoelectric conversion elements.
Citation Information
Patent Citations
Method for preparing rare-earth-element-doped lanthanum-strontium-manganese-oxygen-system manganite magnetic resistance materials
CN104091885A
Titanium ore-structured redox reaction catalyst and preparation method and application thereof
CN108786828A
Ferromagnetic material, preparation method thereof and sensor
CN110580995A
Perovskite type electromagnetic wave absorbing material and preparation method thereof
CN113573561A
Antiferromagnetic sulfur halide crystal and preparation method and application thereof
CN115896949A